Using synergy of experimental and computational techniques to solve monomer–trimer dilemma. (30th December 2014) - Jung, Dubravka Šišak; Hrenar, Tomica; Jović, Ozren; Kalinovičić, Petra; Primožič, Ines
Abstract : An example of commercially available product, 2-(methylideneamino)acetonitrile (MAAN). This paper will address problems in discerning monomer–polymer ambiguity in organic compounds. Reliable three-step analysis of organic polymers will be proposed using the synergy of computational [density functional theory (DFT)] and experimental [infrared spectroscopy (IR); X-ray powder diffraction (XRPD)] techniques. First, possible conformations of monomeric and trimeric MAAN were calculated using stochastic search and DFT. Second, identification of the commercial sample was performed by comparing the measured IR spectrum with those calculated for monomer and trimer. Third, the examination of sample purity and structural analysis were carried out using XRPD data.